2010
DOI: 10.5194/aab-53-436-2010
|View full text |Cite
|
Sign up to set email alerts
|

Selection indexes for genetic improvement of yearling weight in Egyptian buffaloes

Abstract: Abstract. Estimates of genetic and phenotypic parameters for body weight at birth, 3, 6, 9, and 12 months of age, and for preweaning and postweaning average daily gain were computed and used to construct 14 selection indexes to improve the 12-month weight in Egyptian buffaloes. The full index incorporating body weight at birth, 3, 6, 9 and 12 months of age had the highest correlation with aggregate breeding value (rTI=0.63). The correlation fell to 0.62 when body weight at birth and 3 months were omitted from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
11
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 6 publications
3
11
3
Order By: Relevance
“…The pre-weaning and post-weaning growth rate of Nili-Ravi buffalo progeny were 316 and 301 g/day in Pakistan but those were much lower than our observed growth rate in both local and crossed buffalo progeny (Akhter et al, 2012) which might be the result of breed and management variations. But slightly agreed with the findings of Shahin et al (2010) mentioning 490 and 380 g for the mentioned periods in Egyptian local buffalo progenies. The significant difference of daily average growth rate in different years reflected the superiority of semen used in AI including slightly variation in the level of management, availability of good quality feed, temperature and humidity.…”
Section: Average Body Weight Gain Of Buffalo Progeny At Weaning and Ysupporting
confidence: 90%
See 1 more Smart Citation
“…The pre-weaning and post-weaning growth rate of Nili-Ravi buffalo progeny were 316 and 301 g/day in Pakistan but those were much lower than our observed growth rate in both local and crossed buffalo progeny (Akhter et al, 2012) which might be the result of breed and management variations. But slightly agreed with the findings of Shahin et al (2010) mentioning 490 and 380 g for the mentioned periods in Egyptian local buffalo progenies. The significant difference of daily average growth rate in different years reflected the superiority of semen used in AI including slightly variation in the level of management, availability of good quality feed, temperature and humidity.…”
Section: Average Body Weight Gain Of Buffalo Progeny At Weaning and Ysupporting
confidence: 90%
“…Body weight variation ( Figure 1) and comparative study ( Figure 2) of those traits in both indigenous and crossbred buffaloes showed significant differences in both weaning (p <0.001) and yearling (p <0.05) stages. In Egyptian buffalo progeny (Shahin et al, 2010) the average body weights at six and twelve months were recorded as 114 and 179 kg, respectively. These results agreed with our findings for local buffalo.…”
Section: Methodsmentioning
confidence: 99%
“…In Italy, the number of buffaloes has increased due to the demand for particular buffalo milk products and since the buffalo is progressively being acknowledged as dairy cattle (Borghese 2004). In Africa, especially in Egypt, buffaloes are being considered as predominant dairy cattle breed (Mourad & Khattab 2009), and male buffaloes are also being reared and fattened for meat production purposes (Shahin et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Means and heritability estimates for body weight, shank length, keel length and breast girth at 2, 4 and 8 weeks of age and body weight at 10 and 12 weeks of age are presented in Table ( The values for BW w10 and BW w12 were 1673 and 1882 gm, respectively. were lower than the value of 1974 gm obtained on Pekin ducks at 8 weeks old by Shahin and Saleh (1997) and higher than the value of 1490 gm recorded on Khaki Campbell breed at 10 weeks old by Yakubu et al (2015). Difference of breeding and management between flocks would lead to difference in body weights at the same age for the same breed.…”
Section: Means and Heritabilitiesmentioning
confidence: 57%